Multislit electromagnetic trap “Jupiter F” - Lavrent’ev, O.A.; Maslov, V.A.; Krutko, N.A.; Oboznyj, V.P. (Вопросы атомной науки и техники, 2008)
The construction of multislit electromagnetic trap “Jupiter F” with application of ferromagnetic materials to strengthening of a magnetic field, the results of calculations, and the results of experimental investigations of the magnetic field configuration are presented. Представлено конструкцію багатощілинної електромагнітної пастки “Юпітер Ф” з використанням феромагнітних матеріалів для підсилення магнітного поля, результати розрахунків та експериментальних досліджень конфігурації магнітного поля. Представлены конструкция многощелевой электромагнитной ловушки “Юпитер Ф” с применением ферромагнитных материалов для усиления магнитного поля, результаты расчетов и экспериментальных исследований конфигурации магнитного поля.